An iterative approach to evaluating impact of CTSA projects using the translational science benefits model - Swanson, Kera; Stadnick, Nicole A.; Bouchard, Isaac; Du, Zeying; Brookman-Frazee, Lauren; Aarons, Gregory A.; Treichler, Emily; Gholami, Maryam; Rabin, Borsika A. (Frontiers in Health Services, 2025)
IntroductionDemonstrating the relevance and impact of translational research across diverse settings is crucial making the research-to-practice pipeline more efficient. The Translational Science Benefits Model (TSBM) is a framework used to report societal and health impacts of clinical and translational research.MethodsA four-phase process was used to co-develop 12 TSBM Impact Profiles aimed at evaluating the impact of clinical and translational research and disseminating this information among diverse audiences. Content analysis was used to understand common and unique themes related to the TSBM domains and benefits across 12 projects.ResultsAcross the 12 TSBM Impact Profiles, TSBM benefits covered all four TSBM domains (Clinical, Community, Economic, and Policy), with a notable focus on Clinical and Community-related benefits. TSBM Impact Profiles took an average of 9 h to complete, with each phase taking 1–3 h to complete. Common themes included Clinical Innovation and Care Integration, Advancing Health Equity and Accessibility, Community and Stakeholder Engagement, and Policy and Systems-Level Change. Three case exemplars that contextualize findings from the content analysis are presented.ConclusionThis work validates and extends the processes originally developed by the creators of the TSBM and offers a process-oriented example of its successful application at an external institution & CTSA hub. Co-creating TSBM Impact Profiles and documenting their development ensured that information was synthesized for broad dissemination and accessibility. Results highlight an effective process for capturing a multitude of impacts and benefits across diverse research projects with future efforts aimed at expanding the application of this method.